Histopathological Progression and Clinicopathologic Factors Associated with Anogenital Condyloma Acuminata: A Pathological Perspective From a Tertiary Hospital in Indonesia - Karimah Ihda Husnayain; Hermin Aminah Usman; Etis Primastari; Pati Aji Achdiat (Faculty of Medicine, Universitas Airlangga, 2026)
Background: Anogenital condyloma acuminata (CA) is a benign lesion caused by low-risk human papillomavirus (HPV). Although typically benign and non-dysplastic, a subset may undergo histopathological progression. Histopathology is essential not only for diagnosis but also for early detection of malignant transformation. In people living with HIV (PLHIV), immunosuppression may further modify the course of CA. Purpose: To analyze clinicopathologic and sexual behavioral factors associated with HIV status in patients with CA and to evaluate histopathological progression from a pathological perspective. Methods: A retrospective cross-sectional study included 224 patients with histopathologically confirmed CA at Dr. Hasan Sadikin General Hospital, Bandung, between 2023 and 2024. Sociodemographic, clinicopathologic, and sexual behavioral data were retrieved from medical records. Associations with HIV status were analyzed using chi-square or Fisher’s exact tests and multivariate logistic regression. Result: Among 224 patients, 87 (38.8%) were HIV-positive. Bisexual orientation (aOR: 12.52; 95% CI: 1.03–151.98), lesion duration >6 months (aOR: 6.14; 95% CI: 1.74–21.72), and internal lesion location (aOR: 0.17; 95% CI: 0.03–0.88) were independent predictors of HIV positivity. Histopathological progression was identified in 13 patients (5.8%), comprising eight low-grade squamous intraepithelial lesions, three high-grade squamous intraepithelial lesions, and two squamous cell carcinomas. It occured in both HIV-positive (n=3) and HIV-negative (n=10). Conclusion: HIV is highly prevalent among CA patients, with sexual and clinicopathologic factors as significant predictors. The identification of histopathological progression, including malignant transformation, highlights the crucial role of pathology and emphasizes the necessity for routine histopathological evaluation to detect malignant potential.